2021
DOI: 10.3390/life11020120
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Linalool against Isoproterenol-Induced Myocardial Infarction

Abstract: Background: Myocardial infarction (MI), a life-threatening disorder, arises from the imbalance between oxygen supply and myocardial demand. Linalool is a naturally occurring monoterpenes with proved numerous pharmacological actions. This study investigated the cardioprotective effect of Linalool on isoproterenol (ISO)-induced MI in rat models and explored part of the underlying molecular mechanisms. Methods: Rats were divided into five groups; groups I and II served as normal and linalool control groups, Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
(52 reference statements)
1
8
0
1
Order By: Relevance
“…By disrupting critical cysteine residues in Keap-1, oxidative stress reduces the ubiquitination of Nrf2, which translocates into the nucleus and activates the transcription of genes that protect against oxidative damage and inflammation [10]. Nrf2 signaling activation has been implicated in ameliorating druginduced oxidative stress and organ damages [11,13,14]. On the contrary, Nrf2 deficiency was associated with a greater severity of renal damage in a mouse model of ischemic and nephrotoxic AKI [15].…”
Section: Introductionmentioning
confidence: 99%
“…By disrupting critical cysteine residues in Keap-1, oxidative stress reduces the ubiquitination of Nrf2, which translocates into the nucleus and activates the transcription of genes that protect against oxidative damage and inflammation [10]. Nrf2 signaling activation has been implicated in ameliorating druginduced oxidative stress and organ damages [11,13,14]. On the contrary, Nrf2 deficiency was associated with a greater severity of renal damage in a mouse model of ischemic and nephrotoxic AKI [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the rest of them have not yet been confrmed to show any efect on the AP models or been applied in the AP treatment. In fact, lots of evidences showed that β-eudesmol and linalool have obvious antiinfammatory, analgesic, antibacterial, and gastroprotective activities, suggesting that those two compounds may also have potential to treat AP by both alleviating the symptoms and preventing complications of this disease [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis study by Schwingshackl and Hoffmann in 2014, MUFAs may be beneficial to reduce cardiovascular events and death [26]. ISO can cause MI through several mechanisms [2,27,28]. The administration of ISO can cause an increase in Ca 2+ levels in the myocardium, which results in an overstimulation of myocytes, with increased contractility and oxygen demand, causing ATP depletion [5].…”
Section: Histopathological Analysismentioning
confidence: 99%